Bioensayos en especies de bodens con actividad terapéutica - Gorriti Gutiérrez, Arilmi (1998)
Bidens pilosa L. and Bidens pilosa variedad minor of Asteraceae family, are known by the common name of 'amor seco'. The biological assays were started with bioassay of Artemia salina Leach, the Biden species showed both, in aqueous and ethanolic extracts bioactivity. In these species it was carried out the pharmacognosy screening that featured the chemical principies of samples. It was identified carbohidrates, condensed tannins, phenolic compounds, flavonoids, steroids and sesquiterpenic lactons. Through the antiulcerous activity assay it was verified the effective dose for all the samples. The LD50 was determined. The results showed 7494 mglkg, for both species. Bidens pilosa L and Bidens pilosa var. minor, showed practically no toxicity.